Carbon-based composite negative electrode material and preparation method thereof
By using petroleum coke tail powder with small particle size to prepare amphiphilic carbon materials and coated and modified graphite, the problem of insufficient fast charging performance and cycle life of graphite negative electrode materials in lithium-ion batteries is solved, and high capacity is achieved. Low potential platform and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411551909.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
Graphite negative electrode materials have problems with insufficient fast charging performance and cycle life in lithium-ion batteries. This is mainly due to the high-oriented structure of graphite, which leads to slow deintercalation and transmission speed, and the insertion and deintercalation of lithium ions lead to expansion and shrinkage of graphite sheets. , thereby causing pulverization and irreversible capacity loss.
Petroleum coke tail powder with a smaller particle size is prepared by acid mixing method, and it is used to coat modified graphite to form a uniform carbon-based composite negative electrode material. This method does not require organic solvents, has a simple process and is suitable for large-scale industrial production.
The high capacity, low potential platform and good fast charging and cycling performance of carbon-based composite anode materials are achieved, while reducing raw material costs and environmentally friendly processes.
Smart Images

Figure CN119430131A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of electrode material preparation, and in particular, to a carbon-based composite negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used in new energy and other fields due to their high energy density and good cycle performance. Graphite negative electrode materials have the characteristics of high specific capacity and environmental friendliness, and have become one of the most commonly used negative electrode materials on the market. However, the high crystallinity of graphite and the highly oriented graphite layered structure limit the deintercalation and transmission speed of lithium ions between graphite negative electrode sheets, which in turn affects its fast charging performance. The insertion and deintercalation of lithium ions between graphite sheets will cause the volume of graphite sheets to expand and contract, which will cause the pulverization of graphite, and ultimately cause irreversible capacity loss and reduce its cycle life. Summary of the invention
[0003] In view of this, the present application provides a carbon-based composite negative electrode material and a preparation method thereof, wherein the preparation method uses industrial waste petroleum coke tail powder with a small particle size that is difficult to use directly as a raw material to prepare an amphiphilic carbon material with a high degree of oxidation, and then uses the amphiphilic carbon material to coat and modify graphite. The prepared carbon-based composite negative electrode material has a uniform amphiphilic carbon material coating layer, has the advantages of high capacity and low potential platform, and has good compatibility with the electrolyte, and has excellent fast charging performance and cycle performance. In addition, the preparation method is simple, the raw materials are cheap and easy to obtain, and no organic solvent is required in the preparation process. It is green and environmentally friendly and suitable for large-scale industrial production.
[0004] The first aspect of the present application provides a method for preparing a carbon-based composite negative electrode material, comprising:
[0005] The amphiphilic carbon material is prepared by a mixed acid method using petroleum coke tail powder as a raw material; the amphiphilic carbon material is dissolved, kneaded and heat-treated with graphite in sequence to obtain a carbon-based composite negative electrode material precursor;
[0006] The carbon-based composite negative electrode material precursor is carbonized to obtain a carbon-based composite negative electrode material.
[0007] In the embodiment of the present application, the particle size D50 of the petroleum coke tail powder is less than or equal to 5 μm;
[0008] In the embodiment of the present application, the specific surface area of the petroleum coke tail powder is 20m 2 / g-50m 2 / g.
[0009] In the embodiment of the present application, the particle size D50 of the graphite is 7 μm-15 μm.
[0010] In the embodiment of the present application, the particle size D50 of the amphiphilic carbon material is 5 μm-8 μm.
[0011] In the embodiment of the present application, the mass of the amphiphilic carbon material is 1.5%-3% of the mass of the graphite.
[0012] In the embodiment of the present application, the volume of the concentrated sulfuric acid accounts for 70%-90% of the sum of the volumes of the concentrated sulfuric acid and the concentrated nitric acid.
[0013] In the embodiment of the present application, the preparation of the amphiphilic carbon material by the mixed acid method using petroleum coke tail powder as raw material comprises the following steps:
[0014] After mixing petroleum coke tail powder with concentrated sulfuric acid, concentrated nitric acid is added dropwise to perform a first mixing treatment, and after washing and drying, an amphiphilic carbon material precursor is obtained;
[0015] dissolving the amphiphilic carbon material precursor in a sodium hydroxide solution, continuing the second mixing treatment, collecting the upper layer of liquid after sedimentation, and obtaining an amphiphilic carbon material precursor solution;
[0016] A hydrochloric acid solution is added to the amphiphilic carbon material precursor solution, and the amphiphilic carbon material is obtained after washing and drying.
[0017] In the embodiment of the present application, the concentration of the concentrated sulfuric acid is 96%-99%, the concentration of the concentrated nitric acid is 65%-68%, and the solid-to-liquid ratio of the petroleum coke tail powder to the mixed solution of the concentrated sulfuric acid and the concentrated nitric acid is 1g:(0.5mL-10mL).
[0018] In the implementation manner of the present application, the concentration of the sodium hydroxide solution is 0.5 mol / L-1.5 mol / L; the concentration of the hydrochloric acid solution is 0.5 mol / L-1.5 mol / L.
[0019] In the implementation manner of the present application, the kneading time is 1h-2h, and the kneading is performed at room temperature.
[0020] In the embodiment of the present application, the heat treatment is a two-stage heat treatment; the temperature of the first stage of the two-stage heat treatment is 200℃-250℃, and the time is 2h-3h; the temperature of the second stage of the two-stage heat treatment is 500℃-550℃, and the time is 1h-2h.
[0021] In the embodiment of the present application, the kneading further includes drying, the drying temperature is 150° C.-180° C., and the drying time is 2 h-3 h.
[0022] In the embodiment of the present application, the temperature of the carbonization treatment is 1000° C.-1200° C., and the time of the carbonization treatment is 6 h-8 h.
[0023] In the embodiment of the present application, the graphite includes pre-oxidized graphite, and the pre-oxidized graphite is obtained by pre-oxidation treatment of natural graphite.
[0024] The second aspect of the present application provides a carbon-based composite negative electrode material prepared by the preparation method provided in the first aspect, wherein the carbon-based composite negative electrode material is a core-shell structure, including a graphite core and an amphiphilic carbon material coating layer coated on the surface of the graphite core.
[0025] In the embodiment of the present application, the particle size D50 of the carbon-based composite negative electrode material is 10 μm-20 μm.
[0026] In the embodiment of the present application, the specific surface area of the carbon-based composite negative electrode material is 1m 2 / g-2m 2 / g.
[0027] The third aspect of the present application provides a battery negative electrode, including a current collector and a negative electrode active layer loaded on the current collector, wherein the negative electrode active layer includes a carbon-based composite negative electrode material prepared by the preparation method described in the first aspect or the carbon-based composite negative electrode material described in the second aspect of the present application.
[0028] A fourth aspect of the present application provides a battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises the battery negative electrode as described in the third aspect.
[0029] A fifth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery as described in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of a method for preparing a carbon-based composite negative electrode material provided in an embodiment of the present application;
[0031] Figure 2 A schematic diagram of the cross-sectional structure of a carbon-based composite negative electrode material provided in an embodiment of the present application;
[0032] Figure 3 This is a HRTEM (High Resolution Transmission Electron Microscope) photograph of the amphiphilic carbon material coating layer of the modified graphite negative electrode material provided in one embodiment of the present application.
[0033] Description of Figure Numbers
[0034] 100-carbon-based composite negative electrode material; 101-graphite core; 102-amphiphilic carbon material coating layer. DETAILED DESCRIPTION
[0035] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0036] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0037] Graphite negative electrode materials have the characteristics of high specific capacity and environmental friendliness, and have become one of the most commonly used negative electrode materials on the market. However, the high graphitization crystallinity of graphite and the highly oriented graphite layered structure affect its electrochemical performance. The highly oriented lamellar structure of graphite will cause lithium ions to be inserted into the graphite lamellars together with organic solvents during the embedding process. When the organic solvent between the graphite lamellars is reduced, gas will be generated, which will cause the graphite lamellars to peel off. The insertion and deintercalation of lithium ions between the graphite lamellars will cause the volume of the graphite lamellars to expand and contract, causing the graphite to pulverize, which will seriously affect the capacity and cycle life of the graphite negative electrode material. In addition, the lamellar structure of graphite will limit the deintercalation and transmission speed of lithium ions, thereby affecting its fast charging performance. In order to alleviate the above-mentioned problems of graphite negative electrode materials, it is common practice to coat and modify graphite. However, the existing methods have problems such as expensive raw materials, uneven coating, unsuitable for large-scale mass production, and easy to cause environmental pollution.
[0038] In view of the above problems, the present application provides a carbon-based composite negative electrode material and a preparation method thereof. The preparation method uses petroleum coke tail powder, an industrial waste with a small particle size that is difficult to use directly, as a raw material to prepare an amphiphilic carbon material with a high degree of oxidation, and then uses the amphiphilic carbon material to coat and modify graphite. The prepared carbon-based composite negative electrode material has a uniform coating layer of amphiphilic carbon material, which has the advantages of high capacity and low potential platform, and has good compatibility with the electrolyte, and has excellent fast charging performance and cycle performance. In addition, the preparation method is simple, the raw materials are cheap and easy to obtain, and no organic solvent is required in the preparation process. It is green and environmentally friendly and suitable for large-scale industrial production.
[0039] The present invention provides a method for preparing a carbon-based composite negative electrode material. Figure 1 The flowchart of the preparation method comprises:
[0040] S101, using petroleum coke tail powder as raw material and adopting mixed acid method to prepare amphiphilic carbon material;
[0041] S102, dissolving the amphiphilic carbon material, kneading and heat treating it with graphite in sequence to obtain a carbon-based composite negative electrode material precursor;
[0042] S103, carbonizing the carbon-based composite negative electrode material precursor to obtain a carbon-based composite negative electrode material.
[0043] In the embodiment of the present application, amphiphilic carbonaceous material (ACM) refers to a special carbon material with both hydrophilicity and lipophilicity that is soluble in alkaline solution or certain organic solvents, obtained by oxidation, nitration or sulfonation of carbon materials such as asphalt and green coke (petroleum coke, needle coke).
[0044] In this application, petroleum coke refers to the vacuum residue of petroleum, which is cracked and coked at 500℃-550℃ by a coking device to generate black solid coke; petroleum coke tail powder refers to the industrial waste generated in the powder production process of petroleum coke when it is used downstream. The particle size of petroleum coke tail powder is usually small and the powder is very fine. It is impossible to produce qualified products using conventional processes in the future. It is usually regarded as industrial waste and discarded. This application collects these petroleum coke tail powders as raw materials for preparing amphiphilic carbon materials. On the one hand, it can effectively improve the utilization rate of raw materials in the production and preparation process of petroleum coke, avoid the waste of tail powder with utilization value, and effectively reduce the raw material cost of amphiphilic carbon materials while being green and environmentally friendly; on the other hand, the fine powder of petroleum coke tail powder can effectively increase the contact area and active sites of the oxidation reaction of petroleum coke tail powder, effectively improve the oxidation degree of ACM obtained by using it, and then improve the subsequent ACM coating uniformity of graphite and the bonding force between the ACM coating layer and the graphite core.
[0045] In the implementation manner of the present application, the particle size D50 of the petroleum coke tail powder is less than or equal to 5μm. In some specific implementation manners of the present application, the particle size of the petroleum coke tail powder can be, for example, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm. In the present application, the particle size D50 refers to the median particle size, that is, the particle size corresponding to the cumulative particle size distribution percentage of the particles reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. In the present application, the particle size D50 can be measured by a laser particle size analyzer.
[0046] In the embodiment of the present application, the specific surface area of the petroleum coke tail powder is 20m 2 / g-50m 2 In some specific embodiments of the present application, the specific surface area of the petroleum coke tail powder can be, for example, 20 m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g. In the present application, the contact area and active sites of the oxidation reaction of the petroleum coke tail powder can be further increased by controlling the specific surface area of the petroleum coke tail powder within a suitable range, thereby further increasing the oxidation degree of the ACM. In the present application, the specific surface area can be tested by a specific surface area and porosity analyzer, and the test standard refers to the national standard GB / T 19587-2017.
[0047] In some embodiments of the present application, the preparation of an amphiphilic carbon material using petroleum coke tail powder as a raw material by a mixed acid method comprises the following steps:
[0048] S201, mixing petroleum coke tail powder with concentrated sulfuric acid, adding concentrated nitric acid dropwise, performing a first mixing treatment, washing and drying to obtain an amphiphilic carbon material precursor;
[0049] S202, dissolving the amphiphilic carbon material precursor in a sodium hydroxide solution, continuing the second mixing treatment, collecting the upper liquid after sedimentation, and obtaining an amphiphilic carbon material precursor solution;
[0050] S203, adding a hydrochloric acid solution to the amphiphilic carbon material precursor solution, washing and drying to obtain an amphiphilic carbon material.
[0051] In step S201, the concentration of concentrated sulfuric acid is 96%-99%, and the concentration of concentrated nitric acid is 65%-68%. In some specific embodiments of the present application, the concentration of concentrated sulfuric acid can be, for example, 96%, 97%, 98%, 99%, and the concentration of concentrated nitric acid can be, for example, 65%, 66%, 67%, 68%. In the embodiment of the present application, the solid-liquid ratio of the mixed solution of petroleum coke tail powder and concentrated sulfuric acid and concentrated nitric acid is 1g:(0.5mL-10mL). In some specific embodiments, the solid-liquid ratio of the mixed solution of petroleum coke tail powder and concentrated sulfuric acid and concentrated nitric acid can be, for example, 1g:0.5mL, 1g:1mL, 1g:2mL, 1g:3mL, 1g:4mL, 1g:5mL, 1g:6mL, 1g:7mL, 1g:8mL, 1g:9mL, 1g:10mL. The main component of petroleum coke is a polycyclic aromatic compound. This application uses a mixed acid system of concentrated sulfuric acid and concentrated nitric acid to prepare an amphiphilic carbon material. The system will undergo a series of oxidation reactions such as nitration and sulfonation reactions at the side chains or edges of the polycyclic aromatic compound molecules, introducing functional groups such as -NO2 and -SO3H. These functional groups provide hydrophilicity for the amphiphilic carbon material, which is conducive to promoting the dissolution of ACM in subsequent alkaline solutions. This application controls the concentration of each component in the mixed acid system of concentrated sulfuric acid and concentrated nitric acid within a suitable range. On the one hand, it can effectively control the reaction rate of the system and slow down the heating rate caused by the excessive reaction. On the other hand, it can further improve the utilization rate of petroleum coke tail powder. The particle size of the petroleum coke tail powder used to prepare ACM in this application is small, and there are more reactive sites. Therefore, the solid-liquid ratio of the corresponding petroleum coke tail powder to the mixed solution of concentrated sulfuric acid and concentrated nitric acid is also low, that is, the petroleum coke tail powder can be oxidized with less acidic solution to prepare the ACM precursor, further reducing the preparation cost of ACM.
[0052] In the implementation manner of the present application, the volume of concentrated sulfuric acid accounts for 70%-90% of the sum of the volumes of concentrated sulfuric acid and concentrated nitric acid. In some specific implementation manners of the present application, the volume of concentrated sulfuric acid can account for 70%, 75%, 80%, 85%, 90% of the sum of the volumes of concentrated sulfuric acid and concentrated nitric acid. The present application can effectively play the role of concentrated sulfuric acid as an oxidant for sulfonation reaction and a catalyst for nitration reaction by controlling the content ratio of concentrated sulfuric acid and concentrated nitric acid within the above range, and can also ensure its role as a dehydrating agent for the mixed acid system of concentrated sulfuric acid and concentrated nitric acid to a certain extent, thereby obtaining a more stable mixed acid system that is more conducive to the reaction.
[0053] In the embodiment of the present application, the concentrated nitric acid is added dropwise. By controlling the concentrated nitric acid to be added dropwise, the reaction speed and temperature of the system can be further controlled, and the violent reaction of the system caused by the small particle size of the petroleum coke tail powder can be effectively alleviated.
[0054] In an embodiment of the present application, the temperature of the first mixing treatment is 50°C-80°C, and the time of the first mixing treatment is 1h-3h. In some specific embodiments, the temperature of the first mixing treatment may be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and the time of the first mixing treatment may be, for example, 1h, 1.5h, 2h, 2.5h, 3h. The present application can further improve the hydrophilicity of the prepared ACM precursor by controlling the parameters of the first mixing treatment within a suitable range. In an embodiment of the present application, the washing and drying method in step S201 may specifically be filtering through a Buchner funnel and then washing with deionized water until the filtrate is neutral.
[0055] In step S202, the concentration of sodium hydroxide is 0.5mol / L-1.5mol / L. In some specific embodiments, the concentration of sodium hydroxide can be, for example, 0.5mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.5mol / L. The present application can fully dissolve the ACM precursor by controlling the concentration of sodium hydroxide within a suitable range, thereby further improving the yield of ACM.
[0056] In the implementation manner of the application, the temperature of the second mixing treatment is 50°C-80°C, and the time of the second mixing treatment is 1h-3h. In some specific embodiments, the temperature of the second mixing treatment can be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and the time of the second mixing treatment can be, for example, 1h, 1.5h, 2h, 2.5h, 3h. In some implementation manners of the present application, the pH of the system after the second mixing treatment is greater than 12. The present application can further increase the solubility of the obtained ACM precursor in the sodium hydroxide solution by controlling the parameters of the second mixing treatment within a suitable range.
[0057] In step S203, the concentration of hydrochloric acid is 0.5mol / L-1.5mol / L. In some specific embodiments, the concentration of hydrochloric acid can be, for example, 0.5mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.5mol / L. The present application can effectively neutralize the pH value of the system by adding a suitable concentration of hydrochloric acid to the alkaline ACM precursor solution, thereby obtaining a neutral ACM product.
[0058] In the embodiment of the present application, the washing and drying method in step S201 and step S203 can specifically be filtering with a Buchner funnel, washing with deionized water until the filtrate is neutral, and then drying.
[0059] In the embodiment of the present application, the particle size D50 of ACM is 5μm-8μm. In some specific embodiments, the particle size D50 of ACM can be, for example, 5μm, 6μm, 7μm, 8μm. The present application uses petroleum coke tail powder as a raw material and controls the reaction conditions within a suitable range to produce ACM particles with a particle size within the above range, which is further beneficial to the subsequent coating of graphite particles and improves the uniformity of the ACM coating layer.
[0060] In step S102, in the embodiment of the present application, the kneading time is 1h-2h, and the kneading is carried out at room temperature, and the temperature may be 20°C-30°C. In some specific embodiments, the kneading time may be, for example, 1h, 1.5h, or 2h, and the kneading temperature may be, for example, 20°C, 22°C, 25°C, 26°C, 28°C, or 30°C. Controlling the kneading parameters within the above range can allow the graphite particles to be fully and evenly mixed with the ACM solution, thereby further improving the subsequent ACM coating uniformity of the graphite particles. ACM is amphiphilic, i.e., hydrophilic and lipophilic. Therefore, ACM molecules can form a self-assembled coating layer at the interface between water and graphite to make up for the defects of the graphite layered structure, thereby effectively promoting the deintercalation and transmission speed of lithium ions in the negative electrode material, while also limiting the volume expansion of graphite, thereby improving the fast charging performance and cycle performance of carbon-based composite negative electrode materials. At the same time, there are some three-dimensional nanopores in the ACM coating layer formed by the construction of carbon sheets, which provide more channels for lithium ion embedding and can further improve the fast charging performance of the negative electrode material.
[0061] In the implementation manner of the present application, the mass of ACM is 1.5%-3% of the mass of graphite. In some specific implementation manners, the mass of ACM can be, for example, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.5%, 2.6%, 2.8%, 3% of the mass of graphite. The present application controls the feed ratio of ACM to graphite within a suitable range, which can ensure that ACM forms a complete and uniform coating layer with moderate thickness on the surface of graphite particles on the one hand, and can also alleviate the problem of agglomeration due to too much ACM and inability to form a coating layer to a certain extent on the other hand.
[0062] In the embodiment of the present application, a drying step is further included after kneading, and the drying temperature is 150°C-180°C, and the drying time is 2h-3h. In some specific embodiments of the present application, the drying temperature can be, for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, and the drying time is 2h, 2.5h, 3h. Excess water in the system can be removed to obtain a dry ACM and graphite mixed product.
[0063] In some embodiments of the present application, graphite may be artificial graphite or natural graphite. In some other embodiments, graphite includes pre-oxidized graphite, that is, graphite is obtained by pre-oxidation treatment of graphite. Pre-oxidation treatment can increase the number of oxygen-containing functional groups on the surface of graphite, thereby further improving the affinity of graphite with ACM and improving the uniformity of ACM coating of carbon-based composite negative electrode materials. In some specific embodiments of the present application, pre-oxidation treatment may be, for example, placing natural graphite in a chemical vapor deposition (CVD) furnace tube, introducing an oxidizing gas, and heating the graphite for pre-oxidation treatment. The temperature of the pre-oxidation treatment is 600°C-700°C, and the time of the pre-oxidation treatment is 30min-60min. In some specific embodiments, the temperature of the pre-oxidation treatment may be, for example, 600°C, 620°C, 640°C, 650°C, 660°C, 680°C, 700°C, and the time of the pre-oxidation treatment may be, for example, 30min, 35min, 40min, 45min, 50min, 55min, 60min. In some other specific embodiments of the present application, the pre-oxidation treatment can also be carried out by using concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide or perchloric acid as an oxidant for liquid phase oxidation. In some other embodiments of the present application, the degree of pre-oxidation can be further improved by controlling the particle size and specific surface area of the graphite within the relevant range. Preferably, the particle size D50 of the graphite can be 7μm-15μm; the specific surface area of the graphite can be 1.0m 2 / g-2.0m 2 In some specific embodiments of the present application, the particle size D50 of graphite can be, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, and the specific surface area of graphite can be, for example, 1.0 m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 In the embodiment of the present application, the number of oxygen-containing functional groups on the graphite surface can be further controlled by controlling the parameters of the pre-oxidation treatment within a suitable range, thereby further improving the bonding force between the graphite core and the ACM coating layer.
[0064] In the embodiment of the present application, the heat treatment is a two-stage heat treatment. In the embodiment of the present application, the temperature of the first stage of the two-stage heat treatment is 200°C-250°C, and the time is 2h-3h. In some specific embodiments, the temperature of the first stage of the heat treatment can be, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, and the time can be, for example, 2h, 2.5h, 3h. In the embodiment of the present application, the temperature of the second stage of the two-stage heat treatment can be, for example, 500°C-550°C, and the time can be, for example, 1h-2h. The present application can effectively slow down the volatilization and aromatization reaction process of the ACM coating by adopting a two-stage heat treatment, thereby avoiding to a certain extent the aromatization reaction of the ACM coating agent before being mixed evenly due to the rapid heating of the heat treatment process, reducing the possibility of ACM forming graphite flakes alone, and thus improving the coating uniformity of ACM on the graphite surface. In the present application, the relevant parameters of the two-stage heat treatment are controlled within a suitable range, which can further improve the uniformity of ACM coating on graphite and the direct bonding strength between ACM and graphite.
[0065] In step S103, the temperature of the carbonization treatment is 1000°C-1200°C, and the time of the carbonization treatment is 6h-8h. In some specific embodiments, the temperature of the carbonization treatment can be, for example, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and the time of the carbonization treatment can be, for example, 6h, 6.5h, 7h, 7.5h, 8h. Controlling the parameters of the carbonization treatment within the above-mentioned appropriate range can further control the surface performance parameters such as porosity and specific surface area of the obtained carbon-based composite negative electrode material, thereby obtaining a negative electrode material with high capacity and good fast charging performance and cycle performance.
[0066] The preparation method of the carbon-based composite negative electrode material provided in the present application uses petroleum coke tail powder, which is usually regarded as industrial waste, as a raw material to prepare an amphiphilic carbon material. On the one hand, the petroleum coke tail powder is effectively recycled, which is green, environmentally friendly and low in cost. On the other hand, the particle size of the petroleum coke tail powder is small, the powder is fine, and the obtained amphiphilic carbon material has good affinity for graphite. Then, the amphiphilic carbon material is used to coat and modify graphite, and the amphiphilic carbon material coating layer in the obtained carbon-based composite negative electrode material is uniform. The carbon-based composite negative electrode material prepared by this method has the advantages of high capacity and low potential platform of graphite itself, while the coating of the amphiphilic carbon material effectively makes up for the defects caused by the graphite sheet structure and effectively alleviates the volume expansion problem of graphite during the charge and discharge process, thereby significantly improving its fast charging performance and cycle performance. In addition, the preparation method is simple in process and does not require the use of organic solvents in the preparation process, which is green and environmentally friendly and suitable for large-scale industrial production.
[0067] The present application also provides a carbon-based composite negative electrode material prepared by the preparation method provided above. The cross-sectional structure diagram of the carbon-based composite negative electrode material is shown in FIG. Figure 2 As shown, the carbon-based composite negative electrode material 100 is a core-shell structure, including a graphite core 101 and an amphiphilic carbon material coating layer 102 coated on the surface of the graphite core 101. In the present application, the amphiphilic carbon material coating layer 102 coats the graphite core 101 having a lamellar structure, which can effectively coat the edges of the graphite lamellae, make up for the defects of the graphite lamellae structure, promote the deintercalation and transmission speed of lithium ions between the graphite lamellae, and thus improve the fast charging performance of the carbon-based composite negative electrode material. In addition, the coating of the graphite core 101 by the amphiphilic carbon material coating layer 102 can also effectively prevent organic solvents from entering the graphite lamellae and effectively limit the volume expansion of graphite, thereby avoiding the graphite lamellae from falling off or pulverizing to a certain extent, and improving the capacity and cycle life of the carbon-based composite negative electrode material. Compared with other carbon materials, the amphiphilic carbon material is both hydrophilic and oleophilic, has good bonding with graphite, and the obtained amphiphilic carbon material coating layer 102 is evenly coated. In the present application, the coating uniformity of the coating layer of the graphite negative electrode material can be reflected by the confocal Raman distribution value measured by the confocal Raman spectrometer. The smaller the value, the better the coating uniformity of the corresponding coating layer. Specifically, the confocal Raman distribution value is to use the confocal Raman spectrometer to test 2500 positions of each sample, and output the Raman values I at 10%, 50%, and 90% respectively. 10 ,I 50 ,I 90 , confocal Raman distribution value = (I 90 -I 10 ) / I 50 In some specific embodiments of the present application, the amphiphilic carbon material coating layer 102 is as follows: Figure 3 As shown, Figure 3 This is a HRTEM (High Resolution Transmission Electron Microscope) photo of the amphiphilic carbon material coating layer of the modified graphite negative electrode material of an embodiment of the present application, from Figure 3 It can be seen that the amphiphilic carbon material coating layer is a three-dimensional porous structure built by the accumulation of carbon sheets.
[0068] In the embodiment of the present application, the particle size D50 of the carbon-based composite negative electrode material is 10 μm-20 μm. In some specific embodiments of the present application, the particle size D50 of the carbon-based composite negative electrode material can be, for example, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm. In the embodiment of the present application, the specific surface area of the carbon-based composite negative electrode material is 1 m 2 / g-2m 2 / g. In some specific embodiments of the present application, the specific surface area of the carbon-based composite negative electrode material can be, for example, 1 m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2m 2 / g.
[0069] The carbon-based composite negative electrode material provided in the present application uses an amphiphilic carbon material to coat graphite, and the obtained coating layer has uniform thickness and strong bonding with graphite. While having the advantages of high capacity and low potential platform of graphite itself, the carbon-based composite negative electrode material also has good fast charging performance and cycle performance.
[0070] The present application also provides a battery negative electrode, including a current collector and a negative electrode active layer loaded on the current collector, the negative electrode active layer including a carbon-based composite negative electrode material prepared by the preparation method described above or a carbon-based composite negative electrode material provided above. In the embodiments of the present application, the current collector includes but is not limited to any one of copper foil and copper foam. In some embodiments of the present application, the negative electrode active layer also includes a conductive agent, an adhesive, and the like. In the embodiments of the present application, the conductive agent may be any conductive agent known in the art. In some embodiments of the present application, the conductive agent may be, for example, one or more of super carbon black, acetylene black, graphene, and carbon nanotubes. In the embodiments of the present application, the adhesive may be any adhesive known in the art. In some embodiments of the present application, the adhesive may be, for example, one or more of sodium hydroxycellulose, polyvinylidene fluoride, and styrene-butadiene rubber.
[0071] The present application also provides a battery, the battery comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, the negative electrode comprising the battery negative electrode provided above. In the embodiment of the present application, the positive electrode comprises a positive electrode active layer, and the positive electrode active material in the positive electrode active layer is any positive electrode active material known in the art, including but not limited to modified or unmodified lithium iron phosphate, lithium iron manganese phosphate, ternary positive electrode material (such as NCM ternary or NCA ternary), binary positive electrode material, etc.
[0072] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0073] The present application is further described below in multiple embodiments:
[0074] Example 1
[0075] (1) Take 40g of petroleum coke tail powder with a particle size D50 of 5μm as a raw material, add it to 280mL of concentrated sulfuric acid with a concentration of 98% and mix it evenly, then take 120mL of concentrated nitric acid with a concentration of 65%, and add the concentrated nitric acid dropwise to the mixture of the petroleum coke tail powder and concentrated sulfuric acid with a dropper; heat to 80°C and stir to react for 3h. After the reaction is completed, pour the reactant into 1000mL of deionized water to terminate the reaction; then filter and wash the filtrate with deionized water until the pH value is 2-3 to obtain an ACM precursor;
[0076] The ACM precursor was mixed with 1000 mL of a 1 mol / L sodium hydroxide solution, stirred at 80° C. for 1 h to dissolve, and the solution was precipitated and the upper layer of liquid was collected to obtain an ACM precursor solution;
[0077] Add 1000 mL of 1 mol / L hydrochloric acid solution to the ACM precursor solution, adjust the pH value to less than 2, filter with a Buchner funnel, wash with deionized water until neutral, collect the solid matter, and then dry at 100°C to obtain ACM;
[0078] (2) 40 g of the prepared ACM was dissolved in water to obtain an ACM solution, and the ACM solution and 1000 g of artificial graphite with a particle size D50 of 9 μm were added to a kneading pot, kneaded at 25° C. for 2 h, heated to 150° C., and stirred for 2 h to obtain a kneaded material; the kneaded material was added to a converter for a two-stage heat treatment: first, heat treated at 250° C. for 2 h, and then heated to 500° C. for 1 h to obtain a carbon-based composite negative electrode material precursor;
[0079] (3) The carbon-based composite negative electrode material precursor is carbonized at 1150° C. to obtain a carbon-based composite negative electrode material.
[0080] Example 2
[0081] The only difference from Example 1 is that the particle size of the petroleum coke tail powder in step (1) is 3 μm.
[0082] Example 3
[0083] The only difference from Example 1 is that the amount of concentrated sulfuric acid in step (1) is 360 ml, and the amount of concentrated nitric acid is 40 mL.
[0084] Example 4
[0085] The only difference from Example 1 is that the artificial graphite in step (2) is also subjected to pre-oxidation treatment, specifically: natural graphite is placed in a CVD tube furnace, air is introduced at a flow rate of 100 mL / min, the temperature is increased to 600° C. at 3° C. / min, kept warm for 30 min, naturally cooled to the temperature increased, and taken out to obtain pre-oxidized graphite.
[0086] Example 5
[0087] The only difference from Example 1 is that the heat treatment of the mixed material in the converter in step (2) is a one-stage heat treatment, that is, the temperature is directly raised to 500° C. for heat treatment for 2 hours.
[0088] Example 6
[0089] The only difference from Example 1 is that in step (1), concentrated sulfuric acid and concentrated nitric acid are first mixed, and then petroleum coke tail powder is added and stirred.
[0090] Comparative Example 1
[0091] The only difference from Example 1 is that in step (1), petroleum coke with a particle size D50 of 15 μm is used to replace the petroleum coke tail powder.
[0092] Related performance testing methods
[0093] Particle size D50: 0.1 g to 0.2 g of the modified graphite negative electrode material prepared in Examples 1 to 6 and Comparative Example 1 was wetted with 0.1 mL of ethanol, and then water was added to 20 mL. The test was performed using a laser particle size analyzer. The measured results are shown in Table 1.
[0094] Specific surface area: The modified graphite negative electrode materials prepared in Examples 1 to 6 and Comparative Example 1 were tested for specific surface area using a specific surface and porosity analyzer. The test standard referred to the national standard GB / T 19587-2017. The measured results are shown in Table 1.
[0095] Confocal Raman distribution value: Take the modified graphite negative electrode materials prepared in Examples 1 to 6 and Comparative Example 1 as samples, use a confocal Raman spectrometer to test 2500 positions of each sample, and output the Raman values I at 10%, 50%, and 90% respectively. 10 ,I 50 ,I 90 , confocal Raman distribution value = (I 90 -I 10 ) / I 50 The calculated results are shown in Table 1. This value can reflect the coating uniformity of the coating layer of the modified graphite negative electrode material. The smaller the value, the better the coating uniformity of the corresponding coating layer.
[0096] Oxygen content in pre-oxidized graphite: The oxygen content on the surface of pre-oxidized graphite was analyzed using a scanning electron microscope-energy dispersive spectrometer (SEM-EDS). The measured results are shown in Table 1.
[0097] Electrochemical performance test
[0098] The modified graphite negative electrode materials prepared in Examples 1 to 6 and Comparative Example 1 were used as negative electrode materials for batteries, and were uniformly mixed with SBR (styrene-butadiene rubber), CMC (sodium carboxymethyl cellulose), and SP (conductive carbon black) at a mass ratio of 95.5:2:1.5:1 to prepare a negative electrode active slurry, which was coated on a negative electrode current collector copper foil, dried, and rolled to prepare a negative electrode sheet, which was assembled with a metal lithium sheet into a button battery;
[0099] Under the conditions of 0.1C constant current charge and discharge and charge and discharge voltage of 0.05V-2.0V, the first charge and discharge capacity, first coulomb efficiency (first coulomb efficiency = first charge capacity / first discharge capacity*100%) and rate performance (rate performance = battery capacity at 1.2C / battery capacity at 0.05C*100%) of the button battery were tested; the measured results are shown in Table 1.
[0100] Table 1
[0101]
[0102]
[0103] As can be seen from Table 1, compared with Comparative Example 1, the embodiment of the present application uses an amphiphilic carbon material tail powder with a particle size D50 less than or equal to 5 μm to coat and modify graphite. The petroleum coke tail powder of Examples 1-5 of the present application has a smaller particle size and a finer powder quality. The prepared amphiphilic carbon material has a better affinity for graphite, and the prepared carbon-based composite negative electrode material has a more uniform amphiphilic carbon material coating layer, and the electrochemical performance of the carbon-based composite negative electrode material is better, with a higher capacity and a better fast charging performance. And it can be seen from the data of Examples 1 and 5 that the two-stage heat treatment can further improve the first charge and discharge capacity, the first Kunlun efficiency and the rate performance of the carbon-based composite negative electrode material compared to the one-stage heat treatment. It can be seen from the data of Examples 1 and 6 that the addition of concentrated nitric acid by dropwise addition can also further improve the electrochemical performance of the carbon-based composite negative electrode material compared to directly mixing concentrated nitric acid and concentrated sulfuric acid.
[0104] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-based composite negative electrode material, characterized in that: include: The amphiphilic carbon material was prepared by mixed acid method using petroleum coke tail powder as raw material. The amphiphilic carbon material is dissolved, kneaded and heat-treated with graphite in sequence to obtain a carbon-based composite negative electrode material precursor; The carbon-based composite negative electrode material precursor is carbonized to obtain a carbon-based composite negative electrode material.
2. The method for preparing a carbon-based composite negative electrode material according to claim 1, characterized in that: The particle size D50 of the petroleum coke tail powder is less than or equal to 5 μm; the specific surface area of the petroleum coke tail powder is 20 m 2 / g-50m 2 / g.
3. The method for preparing a carbon-based composite negative electrode material according to claim 1 or 2, characterized in that: The mass of the amphiphilic carbon material is 1.5%-3% of the mass of the graphite.
4. The method for preparing a carbon-based composite negative electrode material according to any one of claims 1 to 3, characterized in that: The method of preparing the amphiphilic carbon material by using petroleum coke tail powder as raw material and adopting the mixed acid method comprises the following steps: After mixing petroleum coke tail powder with concentrated sulfuric acid, concentrated nitric acid is added dropwise to perform a first mixing treatment, and after washing and drying, an amphiphilic carbon material precursor is obtained; dissolving the amphiphilic carbon material precursor in a sodium hydroxide solution, continuing the second mixing treatment, collecting the upper layer of liquid after sedimentation, and obtaining an amphiphilic carbon material precursor solution; Adding hydrochloric acid solution to the amphiphilic carbon material precursor solution, washing and drying to obtain the amphiphilic carbon material; The volume of the concentrated sulfuric acid accounts for 70%-90% of the sum of the volumes of the concentrated sulfuric acid and the concentrated nitric acid, the concentration of the concentrated sulfuric acid is 96%-99%, and the concentration of the concentrated nitric acid is 65%-68%; the solid-to-liquid ratio of the petroleum coke tail powder to the mixed solution of the concentrated sulfuric acid and the concentrated nitric acid is 1g:(0.5mL-10mL).
5. The method for preparing a carbon-based composite negative electrode material according to any one of claims 1 to 4, characterized in that: The kneading is carried out at room temperature for 1 h to 2 h; And / or, a drying step is further included after the kneading and before the heat treatment.
6. The method for preparing a carbon-based composite negative electrode material according to any one of claims 1 to 4, characterized in that: The heat treatment is a two-stage heat treatment; the temperature of the first stage of the two-stage heat treatment is 200°C-250°C, and the time is 2h-3h; the temperature of the second stage of the two-stage heat treatment is 500°C-550°C, and the time is 1h-2h.
7. The method for preparing a carbon-based composite negative electrode material according to any one of claims 1 to 4, characterized in that: The temperature of the carbonization treatment is 1000° C.-1200° C., and the time of the carbonization treatment is 6 h-8 h.
8. The method for preparing a carbon-based composite negative electrode material according to any one of claims 1 to 7, characterized in that: The graphite includes pre-oxidized graphite, and the pre-oxidized graphite is obtained by pre-oxidation treatment of graphite.
9. A carbon-based composite negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The carbon-based composite negative electrode material is a core-shell structure, including a graphite core and an amphiphilic carbon material coating layer coated on the surface of the graphite core, and the coating layer has three-dimensional nanopores constructed by a carbon layer.
10. A carbon-based composite negative electrode material as claimed in claim 9, characterized in that: The particle size D50 of the carbon-based composite negative electrode material is 10 μm-20 μm; and / or the specific surface area of the carbon-based composite negative electrode material is 1 m 2 / g-2m 2 / g.
11. A negative electrode of a battery, characterized in that: It comprises a current collector and a negative electrode active layer loaded on the current collector, wherein the negative electrode active layer comprises a carbon-based composite negative electrode material prepared by the preparation method according to any one of claims 1 to 8 or a carbon-based composite negative electrode material according to any one of claims 9 to 10.
12. A battery, characterized in that: The battery comprises a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the negative electrode comprises the battery negative electrode as claimed in claim 11.
13. An electrical equipment, characterized in that: The electric device comprises the battery as claimed in claim 12.
Citation Information
Cited By
Composite material and preparation method thereof, electrode and battery
CN122417848A